Bolton Analysis on Class I, II, and III Malocclusion Cases - Triwardhani, Ari; Alida, Alida; Aulia, Vini Nur (Indonesian Journal of Dental Medicine, 2022)
Background: Tooth size discrepancy is defined as an imbalance in size between each tooth. To obtain good occlusion with overbite and overjet, the maxillary and mandibular teeth must be of the appropriate size. One of the causes of malocclusion is the mismatch of the mesiodistal size of the teeth to the arch of the jaw. The relation of teeth with a large maxillary mesiodistal size while the mandibular mesiodistal size is small, it is impossible to get an ideal occlusion. This condition is known as tooth size discrepancy and can be a problem when determining the orthodontic treatment plan and when achieving the final orthodontic treatment outcome. Purpose:  this study aimed to describe Bolton's analysis in cases of Class I, II, and III malocclusions. Review(s): The literature sources used in preparing the review were through databases PubMed and Google Scholar with the keywords tooth size discrepancy, Bolton analysis, and Class I, II, and III malocclusions.  From the results of the researchers' measurements on malocclusions in the Angle Classification Class I and II, The anterior ratio was different in several cases, while in Class III the results were greater than the Bolton ratio, where the size of the lower jaw teeth was larger than the maxillary teeth, especially in the anterior ratio. Conclusion: Bolton's analysis can be applied to all cases regardless of the type of malocclusion, gender, or race, and remains an important investigation before starting treatment for post-treatment arch stability.